Multikulturalismus v ČR – věc známá či neznámá? - Řízek, Zdeněk (Univerzita Pardubice, 2010)
Multiculturalism is in fact today´s globalized world, but loses its original meaning of world. To take power radicalism and extremism, and a better case and concluded he focused individual cultures into their worlds. This cultural separatism can be hazardous to its explosiveness latent and unresolved problems of different cultures concentrated in large units becomes a sources of ideological, social and even the every day´s conflicts.
Keywords: multiculturalism; globalization; migration; xenophobia; racism; terrorism; education; social programmes